2019
DOI: 10.1038/s41598-019-49746-1
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic liver function measured by LiMAx – a reliable diagnostic and prognostic tool in chronic liver disease

Abstract: Chronic liver disease (CLD) is a major cause of morbidity and mortality worldwide. Non-invasive assessment of hepatic disease severity represents a relevant issue to further improve clinical management and therapeutic treatment. We retrospectively compared the diagnostic and prognostic performance of different non-invasive tools (LiMAx, transient elastography (TE), and biomarkers) in detecting different severity stages during the course of CLD. Patients were divided into four groups based on clinical parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…Different studies have shown that the LiMAx breath test is able to determine enzymatic liver function and therefore can effectively predict outcome in various clinical settings, like for patients undergoing hepatic surgery or patients with acute liver failure 27 30 . In addition, we could demonstrate strong correlation between LiMAx and the degree of chronic liver disease, cirrhosis and portal hypertension in previous studies of our group 32 , 33 . Hence, we evaluated the ability of LiMAx to predict outcome after TIPS placement, in comparison to other, more established parameters.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Different studies have shown that the LiMAx breath test is able to determine enzymatic liver function and therefore can effectively predict outcome in various clinical settings, like for patients undergoing hepatic surgery or patients with acute liver failure 27 30 . In addition, we could demonstrate strong correlation between LiMAx and the degree of chronic liver disease, cirrhosis and portal hypertension in previous studies of our group 32 , 33 . Hence, we evaluated the ability of LiMAx to predict outcome after TIPS placement, in comparison to other, more established parameters.…”
Section: Discussionsupporting
confidence: 72%
“…The liver maximum capacity (LiMAx) breath test is a novel non-invasive quantitative test to measure enzymatic liver function by determining hepatic metabolization of 13 C-labeled methacetin by cytochrome P450 1A2 and was initially evaluated to assess operability of patients undergoing hepatic surgery 27 29 . Still, it was also successfully evaluated for other clinical situations, e. g. estimation of survival of patients with acute liver failure 30 or liver transplant (LT) candidates 31 and for prediction of hepatic disease severity/grade of liver fibrosis 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…LiMAx measurement in patients having surgery while waiting for liver transplantation. 34 It would also be interesting to analyze if surgery and possible complications after surgery have an impact on the likelihood of later successful transplantation.…”
Section: Credit Author Statementmentioning
confidence: 99%
“…Thus, before the examination, the operator should investigate the clinical history to detect symptoms potentially related with altered gastric emptying or conditions affecting the absorption of the substrate from the gastrointestinal tract [ 161 , 162 ]. In this case, the intravenous administration of the substrate (as the LiMAx ® test) can be useful to obtain accurate results, also limiting inter-individual variations in substrate absorption after oral administration [ 163 , 164 , 165 , 166 ].…”
Section: General Features Of Btmentioning
confidence: 99%